The voracious appetites of public versus private property: a view of intellectual property and biodiversity from legal pluralism - Wiber, Melanie G. (International Food Policy Research Institute, 2005)
This paper argues, from the perspective of legal pluralism, that both private and public properties are voracious. In recent western developments, they each expand by trying to 'eating the other up'. Western property theory promotes this dualistic game of voracious property types. In exporting this game world wide through privatization, international agreements and regulations many other more balanced approaches to property, which fall between the public/private divide, are being consumed as well (as in kin group corporate property, cultural property etc.) Such a dualistic model of property limits our understanding of the ways in which the property rights of different claimants are interdependent. This interdependence arises not only from legal institutions that mediate property rights, but also from social institutions that determine and distribute rights, and how these legal and social institutions interface. The three-tiered model presented in this paper--ideological, legal, and social--reveals the systemic nature of property rights. Issues concerning 'new' forms of intellectual property, as well as the management of natural resources, highlight the limitations of the ideological approach to property rights, which largely ignores the legal and social relationships embedded in these forms of property. This paper explores the implications of such voracious property for biodiversity.